METHODICAL PECULIARITIES OF GEOPHYSICAL INVESTIGATIONS OF THE "HANKAYIN DJUR" LANDSLIDE (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
In the article the choice of method and the technique of complex geophysical investigations of the "Hankayin Djur" landslide is discussed with the purpose of investigation of engineering-geological composition and dynamics of landslide body. The suggested complex of geophysical methods will allow to decide setting elements of the same type landslide body. Suggested methods follow the dynamics of the landslide.
Keywords: "Hankayin Djur"; landslide body; engineering-geological composition; dynamics of landslide body